2020
DOI: 10.35940/ijeat.c4727.029320
|View full text |Cite
|
Sign up to set email alerts
|

Marathi Text Analysis using Unsupervised Learning and Word Cloud

Abstract: Managing a large number of textual documents is a critical and significant task and supports many applications ranging from information retrieval to clustering search engine results. Marathi is one of the oldest of the regional languages in the Indo-Aryan language family, dating from about AD 1000. Abundance of Marathi literature has generated a big corpus and need of summarization of information. The objective of this study is to overcome the scalability problem while managing the documents and summarize the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…It was also found that an NLPbased approach may perform poorly for grammatically incorrect text. [5] Performed Sentiment Analysis of Marathi text using Unsupervised Learning composed through Word Cloud visualization. The system summarised the clusters of the Marathi corpus using unsupervised learning, which is the first of its kind.…”
Section: Language-wise Research On Sentiment Analysismentioning
confidence: 99%
“…It was also found that an NLPbased approach may perform poorly for grammatically incorrect text. [5] Performed Sentiment Analysis of Marathi text using Unsupervised Learning composed through Word Cloud visualization. The system summarised the clusters of the Marathi corpus using unsupervised learning, which is the first of its kind.…”
Section: Language-wise Research On Sentiment Analysismentioning
confidence: 99%